2020
DOI: 10.1101/2020.05.13.093724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct large-scale networks are associated with motor and nonmotor symptoms in Parkinson’s disease

Abstract: Parkinson's disease (PD) is characterized clinically by various motor and nonmotor symptoms. The underlying neuroanatomical correlates of nonmotor symptoms in PD remain poorly understood. We investigated the differences and commonalities in the neuroanatomical correlates 1) between highly prevalent nonmotor features including fatigue, anxiety, depression, and apathy, and 2) between these nonmotor features and motor severity in nondemented subjects with mild PD (Hoehn & Yahr disease stage 2) using structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Instead, we selected large-scale regions of interest (ROIs) in light of maximal population level reproducibility and biological validity, while also accommodating for individual anatomic variability. Based on the alterations in large scale brain network associated with motor and nonmotor symptoms of PD 47,48 , we selected five ROIs: the prefrontal cortex, motor cortex, cerebellum, brainstem and the subcortical region including the caudate nucleus, putamen, globus pallidus internus and externus, substantia nigra, thalamus and subthalamic nucleus. The detail of the atlas coordinates and subareas are listed in the supplementary material (Supplementary Table S1).…”
Section: Rs-fmri Region Of Interestsmentioning
confidence: 99%
“…Instead, we selected large-scale regions of interest (ROIs) in light of maximal population level reproducibility and biological validity, while also accommodating for individual anatomic variability. Based on the alterations in large scale brain network associated with motor and nonmotor symptoms of PD 47,48 , we selected five ROIs: the prefrontal cortex, motor cortex, cerebellum, brainstem and the subcortical region including the caudate nucleus, putamen, globus pallidus internus and externus, substantia nigra, thalamus and subthalamic nucleus. The detail of the atlas coordinates and subareas are listed in the supplementary material (Supplementary Table S1).…”
Section: Rs-fmri Region Of Interestsmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (RS-fMRI) of PD patients with depression revealed strong functional connectivity (FC) in the limbic and motor regions and weak FC between the cortical-limbic and corticalcerebellar networks (Hu et al, 2015;Morgan et al, 2018;Liao et al, 2020). Abnormal FC between distinct neural circuits has also been observed even in PD patients with subclinical neuropsychiatric symptoms (Tinaz et al, 2021), and analysis of resting-state FC has shown potential for distinguishing between PD patients who are depressed or not (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%